Transnationale klasser - Trolle, Astrid Krabbe (Religionsvidenskabeligt Tidsskrift, 2023)
ENGLISH ABSTRACT: In a Danish context, Filipino migrants are often positioned as working class laborers from the global South. Yet this political positioning of work migrants does not catch the complex processes of individual social positioning within a transnational space. This article shows how social class is shaped by 1) political mobilization, 2) positions of employment and social status, 3) processes of gendered intimacy, and 4) performances of embodiment. Throughout every aspect, individual and institutional religiosity creates alternative spaces where the established social classes become less important. The interviewed Filipino Christians apply individual narratives of religious endeavour to complement their social situation in Denmark. DANSK RESUMÉ: Filippinske migranter bliver i en dansk kontekst ofte positioneret som ufaglært arbejdskraft fra det globale syd. Men den politiske positionering tager ikke højde for den ofte komplekse individuelle placering i et transnationalt socialt rum. Artiklen viser, hvordan social klasse er formet af 1) politisk mobilisering, 2) erhvervsmæssig placering og social status, 3) kønnede processer i intimsfæren, og 4) kropsliggørelse. I alle aspekter skaber både individuel og institutionel religiøsitet alternative rum, hvor de etablerede sociale klasser bliver mindre vigtige. De interviewede filippinske kristne kultiverer religiøse modnarrativer, der giver andre perspektiver på deres sociale situation i Danmark.